Students’ Learning Experience in Introduction to Drama Theatre Classes During COVID-19 - Muhammad Azri, Ali (UNIMAS Publisher, 2021)
The pandemic has caused the closure of educational institutions, which halted face-to-face teaching and learning. The unprecedented situation has left the institutions with no other choice other than implementing online learning to ensure the educational process's continuity. This study examines students' perceptions in Introduction to Drama and Theatre online classes. Three components of perceptions were investigated: the experience in learning the subject online, students' participation in the class, and the materials used in online classes. The quantitative data were collected from 38 first-year students enrolling in the Drama and Theatre programme at UNIMAS. The questionnaire was distributed online using Google Form. The findings showed a positive perception of learning Introduction to Drama and Theatre online, while moderate perception was identified in students' participation in the class. A positive perception was also seen in the materials and platforms used in online classes. Most of the students enjoyed the learning process due to the support from the lecturer. Moving forward, better infrastructure is needed in order to ensure the ability to conduct online learning without any obstacles. All stakeholders are responsible for playing their role to contribute to the online learning environment.